Identification of a Broadly Active Phage Lytic Enzyme with Lethal Activity against Antibiotic-Resistant Enterococcus faecalis and Enterococcus faecium - Yoong, Pauline (American Society for Microbiology, 2004)
Enterococcus faecalis and Enterococcus faecium infections are increasingly difficult to treat due to high levels of resistance to antibiotics. PlyV12, a bacteriophage lytic enzyme, was isolated and shown to effectively kill both E. faecalis and E. faecium (including vancomycin-resistant strains), as well as other human pathogens. We propose its development and use as an alternative therapeutic tool.